Taxonomic and functional profiling of the vulvar microbiome indicates variations related to ecological signatures, aging, and health status - Mieremet, Arnout; van der Wurff, Michelle; Pagan, Lisa; Ferrer-González, Edgar; Seo, Jin; Schuren, Frank H. J. (Frontiers in Microbiology, 2025)
IntroductionThe vulvar microbiome is adjacent to that of the skin and the vagina and connects microbiomes present on a stratified epithelial barrier to that of a mucosal barrier. Yet, the characterization of the microbiome in the vulvar region of the body is understudied, although dysbiosis in the microbiome of the skin or vagina have been linked to impairments in women’s health.MethodsTo better understand the role of the vulvar microbiome during healthy aging or during presentation of vulvar diseases, we analyzed the vulvar microbiome by shotgun metagenomic sequencing on composition at species level and for functional capacity. This was performed in a large population enrolled in the Vulvar Microbiome Leiden Cohort (VMLC), including a total of 58 healthy women in a broad age range (22–82 years). Moreover, we analyzed vulvar microbiome derived from 9 participants presenting a vulvar disease, including vulvar lichen sclerosus (LS; N = 6), or high-grade squamous intraepithelial lesion (HSIL; N = 3).ResultsCompositional analyses showed a skin-, vagina-, or multispecies mixture- dominant bacterial signature, which revealed differences in the alpha diversity and functional capacity of the microbiome. Upon aging the presence of Lactobacillus iners, L. crispatus, and L. gasseri in the vulvar microbiome shifted toward reduction. In the microbiome of individuals with a vulvar disease, higher abundance of Staphylococcus hominis, Micrococcus luteus, Corynebacterium amycolatum, and Corynebacterium simulans was detected, and an altered functional capacity for the L-histidine pathway.DiscussionIn conclusion, we identified variations in microbial taxa and functional capacities in the vulvar microbiome that are associated with age and disease (LS and HSIL), which can be targeted to develop microbiome-based vulvar therapies promoting women’s health.